The Phenomenon of Online Gender-Based Violence Among Instagram Second Account Users - Dwi Agustini, Vilya; Setiawati, Titin; Praptiningsih, Novi Andayani (Communication, 2026)
The rapid growth of internet users in Indonesia not only has positive impacts but also increases the risk of of Online Gender-Based Violence (OGBV). Inadequate digital literacy increases the vulnerability of social media users to violence and privacy violations in the digital space. The study aims to explore the potential for KGBO and identify various forms of violence experienced by Second Account users on Instagram. A qualitative method with a phenomenological approach was employed to explore the subjective experiences of Second Account users who were victims of violence, through various Instagram features such as direct messages, comments, or the sharing of inappropriate content. The findings of this study reveal that the digital space is not entirely safe, control over self-image is vulnerable to manipulation, and the risk of violence is experienced across genders, by both women and men. The impact of KGBO manifests itself in the form of psychological disturbances in the real world, including chronic anxiety, depression, loss of a sense of security, and fear of self-expression.